Scientometric Mapping of Global Scientific Production on Obstetric Violence: Visualization, Emerging Patterns, and Collaborative Networks - Victor Roman-Lazarte; Raquel Flor De María Tumialan-Hilario; Frank Mayta-Tovalino (Journal of Client-centered Nursing Care, 2025)
Background: Obstetric violence is defined as mistreatment or disrespect toward women in health care facilities, especially in obstetric care. It is a common problem that can occur across all health care facilities. This study aims to evaluate the global scientific production of obstetric violence in the Scopus database, visualizing emerging patterns, identifying key terms and trending topics, and mapping collaborative networks. Methods: A bibliometric analysis of the scientific production on obstetric violence in the Scopus database was conducted between 2000 and 2024. The keywords were identified based on the principle of exhaustiveness, and Zotero was used to manage the references. An analysis was performed regarding production by year and country. Also, countries and author collaboration were identified. Additionally, emerging terms and the co-occurrence of keywords most frequently used by authors were identified. A general description of the 10 most-cited articles up to the search date was also provided. Data were analyzed using VOSviewer software, version 1.6.20, and RStudio, version 4.4.2. Results: Regarding visualization, scientific production shows steady growth, especially from 2014 onwards (R²=0.95). About emerging patterns, the most frequent keywords were “obstetric violence,” “disrespect,” and “mistreatment.” The main collaboration networks were between Ghana, Sweden, and Guinea. The most cited article was “The mistreatment of women during childbirth in health facilities globally: A mixed-methods systematic review,” with 900 citations, published in 2015. Conclusion: Obstetric violence is an emerging research topic, and international collaboration primarily occurs between geographically neighboring countries. It is recommended that countries that have not yet explored this phenomenon take the initiative to gain a better global perspective.